Integration of Artificial Intelligence in the Islamic Religious Education Curriculum at Ibnurusyd Islamic College, Lampung - Roni Susanto; Mariyatul Kiftiyah (LP3M Pascasarjana STAI Ibnurusyd, 2025)
This study aims to analyze the integration of artificial intelligence (AI) technology in the Islamic Religious Education (PAI) curriculum at the Ibnurusyd Islamic College (STAI) in Lampung. The development of digital technology, particularly AI, has brought significant changes to the world of education, including religious education. AI integration is expected to improve learning effectiveness, enrich learning resources, and expand student access to more interactive and contextual Islamic knowledge. This study uses a descriptive qualitative approach with a case study method, involving in-depth interviews with lecturers, students, and curriculum managers, as well as analysis of Semester Learning Plan (RPS) documents and academic policies. The results show that the implementation of AI in the PAI curriculum is still partial, in the form of the use of chatbot applications, AI-based e-learning, and the use of big data for analyzing student understanding. However, there is no specific curriculum standard that regulates the comprehensive integration of AI in PAI learning. This study recommends the development of an adaptive curriculum that integrates AI with the principles of religious moderation, as well as improving lecturers' competencies in digital literacy and AI technology for optimal implementation.